2007
DOI: 10.1152/ajpheart.01002.2006
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of cardiac insulin signaling and myocardial contractile performance in high-cholesterol/fructose-fed rats

Abstract: Deng J-Y, Huang J-P, Lu L-S, Hung L-M. Impairment of cardiac insulin signaling and myocardial contractile performance in high cholesterol-fructose-fed rats. Am J Physiol Heart Circ Physiol 293: H978-H987, 2007. First published March 30, 2007; doi:10.1152/ajpheart.01002.2006.-Although insulin resistance is recognized as a potent and prevalent risk factor for coronary heart disease, less is known as to whether insulin resistance causes an altered cardiac phenotype independent of coronary atherosclerosis. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 44 publications
2
40
0
Order By: Relevance
“…To mimic Western eating habits characterized by consuming a high-cholesterol diet combined with sugarsweetened beverages, we fed rats with a high-cholesterol diet combination with 10% fructose in drinking water (HCF diet) for 15 weeks and found that these rats could develop a phenotype of insulin resistance syndrome characterized by an increase in blood pressure, hyperlipidemia, hyperinsulinemia, and impaired glucose tolerance with relative normal body weight gain, as previously described (15). Since the beneficial effects of RSV on obesity and insulin resistance were functionally intertwined in an obesity-induced insulin-resistant animal model (12,13), HCF diet-fed rats instead of obese rats were chosen in the present study to test whether ER signaling is directly involved in the effects of RSV on diet-induced whole-body and muscular insulin resistance without the potential disturbance of RSV-mediated anti-obese effect to data interpretation.…”
mentioning
confidence: 99%
“…To mimic Western eating habits characterized by consuming a high-cholesterol diet combined with sugarsweetened beverages, we fed rats with a high-cholesterol diet combination with 10% fructose in drinking water (HCF diet) for 15 weeks and found that these rats could develop a phenotype of insulin resistance syndrome characterized by an increase in blood pressure, hyperlipidemia, hyperinsulinemia, and impaired glucose tolerance with relative normal body weight gain, as previously described (15). Since the beneficial effects of RSV on obesity and insulin resistance were functionally intertwined in an obesity-induced insulin-resistant animal model (12,13), HCF diet-fed rats instead of obese rats were chosen in the present study to test whether ER signaling is directly involved in the effects of RSV on diet-induced whole-body and muscular insulin resistance without the potential disturbance of RSV-mediated anti-obese effect to data interpretation.…”
mentioning
confidence: 99%
“…The basal FATP1 (fatty acid transporter 1) levels were increased in HCF rat hearts. The cardiac performance of the HCF rats showed a marked reduction (25). Our results indicate that high-cholesterol food and sugar-sweetened beverages that lead to maladaptive metabolic processes may interfere with the action of insulin and increase susceptibility for the development of cardiomyopathy (25).…”
Section: High Cholesterol and Fructose Diet (Hcf)mentioning
confidence: 81%
“…Our laboratory study reveals that a high cholesterol-fructose (HCF) diet also induces insulin resistance not only in metabolicresponsive tissues (i.e. liver and muscle) but also in the heart as well (25). Insulin-stimulated cardiac glucose uptake was significantly reduced after 15 weeks of HCF feeding, and cardiac insulin resistance was associated with blunted Akt-mediated insulin signaling along with GLUT4 translocation.…”
Section: High Cholesterol and Fructose Diet (Hcf)mentioning
confidence: 92%
See 1 more Smart Citation
“…In the heart, metabolic flexibility is its ability to alter fuel oxidation to fuel availability [47]. Under insulin resistant conditions, an impairment of insulin signaling occurs, followed by reduced glucose uptake and reduced ability of the heart to use glucose as a substrate for ATP production [48]. Thus, a large amount of FFA is delivered to the heart, and it has been implicated in the accumulation of intracellular lipids.…”
Section: Effects Of Obese-insulin Resistance On the Heart Subject To mentioning
confidence: 99%